1989
DOI: 10.1037/0278-7393.15.2.188
|View full text |Cite
|
Sign up to set email alerts
|

Sensory-perceptual qualities of images.

Abstract: Four experiments demonstrated that such sensory-perceptual features of objects as weight, color, and numerosity affect imaginal performance involving images of those objects. For example, imaginary transport times of objects increased with both the hypothetical weight of the imagined object and the distance traversed. The transport functions were steeper when a map of the terrain was imagined than when it was perceived, suggesting that imaginal performance of heft did not parallel more perceptually guided perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…Other researchers have found that the details of the mental simulation exercise influence performance (e.g., Intons-Peterson & Roskos-Ewoldsen, 1989;Taylor et al, 1998). For example, Intons-Peterson and Roskos-Ewoldsen asked people to mentally travel specified routes and to press a button when they arrived at the destinationpoint.…”
Section: Experiments 2a-2cmentioning
confidence: 99%
“…Other researchers have found that the details of the mental simulation exercise influence performance (e.g., Intons-Peterson & Roskos-Ewoldsen, 1989;Taylor et al, 1998). For example, Intons-Peterson and Roskos-Ewoldsen asked people to mentally travel specified routes and to press a button when they arrived at the destinationpoint.…”
Section: Experiments 2a-2cmentioning
confidence: 99%
“…To see the basis for the dispute, suppose that subjects in an experiment take a specific amount of time to infer how long it will take them to walk 30 yards. Also suppose that when subjects are told they will be carrying a heavy backpack, it takes them longer to make their inference (Decety, Jeannerod, & Prablanc, 1989;Intons-Peterson & Roskos-Ewoldsen, 1989). An analog characterization of this backpack effect might be that people incorporate weight information into their imagery.…”
Section: A Task For Investigating Physical Imagerymentioning
confidence: 99%
“…This explanation has much in common with the knowledge-weighting model proposed by Intons-Peterson and her colleagues (Intons-Peterson & McDaniel, 1991;Intons-Peterson & Roskos-Ewoldsen, 1989), though they assume that the information retrieved from memory is in a canonical form. Relying on previous work (Hubbard et aI., 1989), we favor an explanation that has subjects retrieving memories of specific episodes from the past, more along the lines envisioned by Tulving (1983).…”
Section: Sensory Interpretationmentioning
confidence: 79%